A decade of fast radio bursts. (November 2018) - Lorimer, Duncan
Abstract Modern astrophysics is undergoing a revolution. As detector technology has advanced, and astronomers have been able to study the sky with finer temporal detail, a rich diversity of sources that vary on timescales from years down to a few nanoseconds has been found. Among these are fast radio bursts, which exhibit pulses of millisecond duration and anomalously high dispersion compared to Galactic pulsars, first seen a decade ago. Since then, a new research community has been actively working on a variety of experiments and developing models to explain this new phenomenon, and devising ways to use them as astrophysical tools. In this Perspective, I describe how astronomers have reached this point, review the highlights from the first decade of research in this field, give some current breaking news, and look ahead to what might be expected in the next few years. The first fast radio burst (FRB) was discovered in 2007, and in the following decade 25 more were detected. Now the field stands on the brink of an explosion of detections, largely driven by the availability of new radio facilities. One of the founders of the field, Duncan Lorimer, reviews the early years of FRB science.